Infeccção experiental de equinos (Equus cabalus) e mures (Equus asinus x Equus caballus) com o vírus da anemia infecciosa equina - André Barbosa Maciel (2008)
Introduction: AIE is a disease that only affects animals from the Equidae family, being caused by a virus belonging to the genus Lentivirus, and the Retroviridae family. A greater prevalence of the virus is recorded in geographic areas with hot and humid climates, reflecting the importance of transmission by hematophagous tabanid insects of the Diptera order. Currently, AIE is an obstacle to the development of equine farming, due to its transmissible and incurable nature, causing losses to owners who need the work of these animals and to breeders interested in improving breeds. Objective: to compare the dynamics of equine anemia virus infection in horses and mules, to verify whether there are differences in infection between the two species. Material and method: The present experiment was carried out in two stages. In the first stage, procedures related to the inoculation of animals with the AIE virus and the obtaining, aliquoting and storage of the samples obtained were carried out, as well as the subsequent euthanasia of the animals. The second stage involved serological tests (IDGA and ELISA). Results: Horses: the animals showed a reduction in the number of platelets after the fever peak and in hematocrit, indicating a mild hemolytic anemia. No noteworthy changes were observed in any other parameter assessed in the blood count. Mules: although there were some variations in the parameters evaluated, in general, the animals did not show signs that demonstrated infection with VAIE. Horses versus Mules: It was observed that horses presented fever peaks around the 40th day PI, as well as a sharp drop in the number of platelets and hematocrit values, while mules, on average, did not show changes in normal parameters of temperature, platelets and hematocrit. Discussion: Animals infected with VAIE may present, during the acute phase of the disease, febrile episodes of varying intensity, thrombocytopenia, hemolytic anemia, prostration, anorexia, weight loss, ventral edema, alopecia, epistaxis and sometimes neurological changes. The occurrence of more severe EIA symptoms appears to be associated with febrile episodes with temperature spikes, above 40.5ºC, which are associated with more intense viral replication and consequently a greater load of viral RNA in plasma. The vast majority of animals infected with VAIE recover after a variable period of days and remain clinically healthy for days or weeks, until they present recurrent episodes of fever, thrombocytopenia and prostration. After 12 months after infection, most animals stop showing clinical signs of infection and enter the asymptomatic phase of the disease, becoming inapparent carriers of the virus and becoming an important source of infection within herds. It suggests that some equine species and equine breeds are more resistant to certain infections than others. Furthermore, it is widely reported by breeders and people who work directly with animals that Pantanal horses and mules are more resistant to showing clinical signs of AIE. Conclusions: Mules are more resistant to clinical manifestations caused by VAIE adapted to horses. Pantanal horses present the classic symptoms associated with VAIE. ELISA is more efficient in detecting anti-AIAV antibodies, both in mules and horses.